Do It Again: Sequences in Gershwin and Kern’s Popular Songs - Maxwell Ramage (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2016)
Melodic sequences can create musical unity, enhance extra-musical drama, and make a piece memorable. In constructing their popular songs for Broadway and Hollywood, Gershwin and Kern both employed melodic sequences, but did so in mutually differing ways. This article opens with a broad-brushed comparison between the composers’ most popular songs and finds that Kern had a greater predilection for sequences than did Gershwin. Next, I closely analyze several songs by each composer in order to specify differences between the two songsmiths’ approaches to sequence. It is determined that Gershwin often reserves melodic sequence for musical climaxes, whereas Kern tends to open his songs with sequences. Finally, the article’s findings are used to critique a strand of Gershwin reception that views his songs as dry or academic.
Keywords: Gershwin; Kern; Sequence; Popular Music; Analysis; Harmony; Melody